PENGELOLAAN SAMPAH BERBASIS SEKOLAH DASAR DENGAN PENDEKATAN KOMPOSTING TAKAKURA DI KOTA JAMBI - Andy Amir; Guspianto Guspianto; Oka Lesmana S (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2019)
Community service has been carried out at the Paal X Health Center in Jambi City, which is a partner of FKM Unja to conduct socialization and training on organic waste management to elementary school teachers and students in the Puskesmas working area. Implementation of five months of service from July to November 2019. The aim is to increase awareness and motivation of elementary school teachers on the importance of empowering students to process waste in the school environment. This service method is a socialization of school-based waste management and training in processing organic waste into compost fertilizer. The results of this service are increasing teacher understanding after getting school-based waste management socialization and teachers and students are able to process organic waste into compost using the Takakura method after get training on compost making. Making compost using materials and tools that are easily available include: basket, cardboard, rice husk pillow, soil as a starter, EM4 bioactivator to accelerate decomposition, and wet and dry organic waste collected by students from the school environment. School-based waste management must have the support of leadership policies so that it can be implemented sustainably so as to reduce waste generation in the environment.